Evaluation of ongoing Crested Ibis (Nipponia nippon) reintroduction using an integrated population model and Bayesian population viability analysis - Okahisa, Yuji; Nagata, Hisashi (Ibis (London, England), 2022)
Reintroduction has often been used as a technique for re‐establishing self‐sustaining animal populations that have become extinct within their indigenous range. To achieve conservation success, it is essential to accurately assess the demographic parameters and the IUCN Red List criteria of the population. However, acquiring data on all indicators and estimating criteria according to established definitions can be challenging. Here, we developed an integrated population model (IPM) and population viability analysis (PVA) framework to estimate all demographic parameters and criteria for a reintroduced population of Crested Ibis Nipponia nippon, and to project population dynamics under a range of release scenarios on Sado Island, Japan. Our IPM‐PVA framework integrated roost count and mark–resight data for 415 released and 203 wild‐hatched individuals, as well as reproductive performance for a total of 575 pairs. We aimed to assess survival, reproductive success, population size, number of mature individuals and population projection. In the first year after release, the estimated apparent annual survival rate was 0.566 [Bayesian credible intervals (CRI) 0.518–0.614]; however, this rate increased after 1 year (0.865; CRI 0.836–0.892). Wild‐hatched juveniles exhibited a high survival rate (0.757; CRI 0.670–0.838) that was just lower than that of adults (0.899; CRI 0.844–0.949). The reproductive success rate varied with pair attributes (released–released pair: 0.245, CRI 0.194–0.299; released–wild pair: 0.377, CRI 0.281–0.471; wild–wild pair: 0.350, CRI 0.237–0.471). Total population size was estimated to be 457 individuals (CRI 384–525), with 261 mature individuals (CRI 211–304) in June 2021. The probability of Crested Ibis extinction in the next five generations was 0%, even if the release was discontinued. Our comprehensive case study demonstrated the effectiveness of IPM‐PVA for the evaluation of ongoing reintroduction programmes.